What can possibly go wrong? The risks of introducing soil microorganisms from Antarctica into South America = ¿Qué puede salir mal? : Los riesgos de introducir microorganismos del suelo de la Antártida en América del Sur - Nuñez, Martin Andrés; Dimarco, Romina Daniela; Dickie, Ian A.; Pauchard, Aníbal (2017)
Endophytic fungi form mutualistic associations with plant roots which can increase plant survival and resistance to stress. Recently, it has been proposed that endophytic fungi from Antarctica should be used to facilitate reintroduction and establishment of native plants in xeric environments of northern Chile. In this note, we suggest this is a risky proposition and may lead to biological invasions. It is difficult to predict which endophytic fungi will become invasive, where they will invade, or what their impacts will be. Organisms that move across continents may or may not become invasive depending on the interaction between the species and the invaded community; unexpected outcomes may occur due to adaptation and novel interactions of the introduced species in the new environment. The fact that these endophytes are mutualistic does not imply that they will not have negative effects on the recipient community, since they might promote invasion of other non-native species or may change the competitive relationships among native species. Further, taxonomically uncharacterized fungal isolates from plant roots are likely to contain non-beneficial species. The fact that these endophytic fungi species are from Antarctica does not ensure that they cannot invade elsewhere. It should be recognized that invasive microorganisms are extremely difficult to control. We strongly suggest that the further translocation, use and spread of endophytes from Antarctica should be halted until a risk assessment is undertaken. Biosecurity measures must be taken when considering transcontinental experiments. Based on previous experiences, it is likely that the risk and potential costs of introducing these new species significantly exceed any potential benefits of their introductions